Analisis Kinerja Pendamping Sosial PKH dalam Pelaksanaan Program di Provinsi Lampung - Mohammad Khairul Idaman; Ahmad Tohir (Universitas Dehasen Bengkulu, 2025)
The Family Hope Program (PKH) is a form of conditional social assistance that has proven effective in improving the quality of life of poor families in various regions of Indonesia. In Lampung Province, this program plays a strategic role in poverty alleviation efforts while strengthening community social resilience, particularly in rural areas that still face limited access to basic services. The policy direction of the PKH Lampung 2025–2030 program focuses on building independent families through increasing economic capacity, education, and health. The program's primary target group is nearly 400,000 Beneficiary Families (KPM), with priority given to households with school-age children, pregnant women, the elderly, and people with disabilities. This research uses a case study approach, emphasizing the implementation strategy of the PKH Lampung 2025–2030 program, which integrates the use of data, technology, and multi-stakeholder collaboration. A SWOT analysis is applied to assess the program's strengths, weaknesses, opportunities, and threats, particularly in practice in Tanjung Harapan Village, Central Lampung. Field studies demonstrate the success of empowering beneficiary families (KPM) through synergy with social services, entrepreneurship training, and the development of cooperative-based sewing and garment businesses marketed through digital platforms. The research confirms that the role of PKH social facilitators significantly contributes to increasing the program's effectiveness, although challenges remain in human resource capacity and cross-sector coordination. Therefore, strengthening competencies through tiered training, providing proportional incentives, integrating economic empowerment programs, a digitalization roadmap, and participatory monitoring are crucial steps. With this strategy, the effectiveness of PKH in Lampung can be sustained while reducing the community's dependence on aid.